2012
DOI: 10.1021/jp304298c
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism for the Preferential Exclusion of TMAO from Protein Surfaces

Abstract: Trimethylamine N-oxide (TMAO) is a naturally occurring protecting osmolyte that stabilizes the folded state of proteins and also counteracts the destabilizing effect of urea on protein stability. Experimentally, it has been inferred that TMAO is preferentially excluded from the vicinity of protein surfaces. Here, we combine computer modeling and experimental measurements to gain an understanding of the mechanism of the protecting effect of TMAO on proteins. We have developed an all-atom molecular model for TMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
231
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(251 citation statements)
references
References 69 publications
14
231
2
Order By: Relevance
“…Urea has a hydration shell spanning 1.3 Å [at g(r) = 1], whereas TMAO has a hydration shell spanning 1.9 Å. Moreover, TMAO has been reported to stabilize native peptide states by acting as a molecular crowder (15,17), as well as by virtue of being depleted from the surface as the protein adopts its native state (18,19). Our earlier computational studies on bulk TMAO showed that the osmolyte's methyl groups did not act as conventional hydrophobic moieties, in agreement with the experiments of Sagle (18), which demonstrated that the methyl groups of TMAO oriented away from hydrophobic surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Urea has a hydration shell spanning 1.3 Å [at g(r) = 1], whereas TMAO has a hydration shell spanning 1.9 Å. Moreover, TMAO has been reported to stabilize native peptide states by acting as a molecular crowder (15,17), as well as by virtue of being depleted from the surface as the protein adopts its native state (18,19). Our earlier computational studies on bulk TMAO showed that the osmolyte's methyl groups did not act as conventional hydrophobic moieties, in agreement with the experiments of Sagle (18), which demonstrated that the methyl groups of TMAO oriented away from hydrophobic surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…However, TMAO molecules are found to be excluded from various protein backbone and sidechain units, thus destabilizing the unfolded state (59). Moreover, many studies have shown that both TMAO and urea can alter the structure and dynamics of the H-bonding network of water, thus resulting in a change in protein stability (69).…”
Section: Discussionmentioning
confidence: 99%
“…Solvation studies with model compounds have suggested that TMAO is excluded from unfolded proteins because of its very unfavorable interactions with the peptide backbone (9, 10). Several molecular dynamics (MD) simulation studies have been consistent with this conclusion (11,12). However, they have proposed a wide array of explanations for this preferential hydration ranging from unfavorable electrostatic interactions (13,14) to "nanocrowder" effects (15,16).…”
mentioning
confidence: 84%